2020
DOI: 10.1177/2515841420913014
|View full text |Cite
|
Sign up to set email alerts
|

Approaches toward enhancing survival probability following deep anterior lamellar keratoplasty

Abstract: The greatest advantage of deep anterior lamellar keratoplasty over full-thickness corneal transplantation is the elimination of graft failure caused by endothelial rejection. Despite this advantage, a deep anterior lamellar keratoplasty graft can fail because of several factors, such as complications related to the donor–recipient interface, graft epithelial abnormalities, graft vascularization, stromal graft rejection, and recurrence of herpetic keratitis. Increased deep anterior lamellar keratoplasty graft s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 137 publications
(225 reference statements)
0
5
0
Order By: Relevance
“…Corneal grafts can also be a source of HSK infection if not properly screened[ 224 ]. With a global shortage of available viable cornea graft tissue, Li et al [ 225 ] demonstrated that porcine corneal tissue is a good option for human corneal tissue[ 225 ], Recurrent HSK has been implicated in Deep Anterior Lamellar Keratoplasty failure[ 226 ]. It is therefore important to differentiate between HSV-linked endotheliitis and actual graft rejection[ 227 ].…”
Section: Recurrent Herpes Simplex Keratitis: Clinical Features and Pr...mentioning
confidence: 99%
“…Corneal grafts can also be a source of HSK infection if not properly screened[ 224 ]. With a global shortage of available viable cornea graft tissue, Li et al [ 225 ] demonstrated that porcine corneal tissue is a good option for human corneal tissue[ 225 ], Recurrent HSK has been implicated in Deep Anterior Lamellar Keratoplasty failure[ 226 ]. It is therefore important to differentiate between HSV-linked endotheliitis and actual graft rejection[ 227 ].…”
Section: Recurrent Herpes Simplex Keratitis: Clinical Features and Pr...mentioning
confidence: 99%
“…Endothelial rejections do not occur as the recipient retains their own Descemet's membrane and endothelium, but epithelial, subepithelial, and stromal reactions are still possible [77,78,143]. DALK rejection rates range from 0 to 21.2% with up to 10 years of follow-up (Table 2) [45,46 ▪ ,64 ▪ ,65,66,68,77–81,83,84,134 ▪▪ ,140 ▪▪ ,144]. Rejection risk in DALK is highest during the first year and subsides as the host epithelial cells and keratocytes repopulate the donor tissue but several studies report an average time-to-rejection between 1 and 2 years [35,45,65,77–79,84,144].…”
Section: Understanding Rejection Riskmentioning
confidence: 99%
“…Data from [35,38,59,77,78,92,95,97,112,131–133,134 ▪▪ ,135 ▪ –137 ▪ ,138 ▪▪ ]. DALK, deep anterior lamellar keratoplasty; DMEK, Descemet's membrane endothelial keratoplasty; DSAEK, Descemet's stripping endothelial keratoplasty; HSV-1, herpes simplex virus 1; IOL, intraocular lens; PKP, penetrating keratoplasty.aIncludes bullous keratopathy, severe dry eye disease, ocular mucous membrane pemphigoid, Steven–Johnson syndrome, chemical injury.…”
Section: Understanding Rejection Riskmentioning
confidence: 99%
“…[ 2 ] Conventionally, penetrating keratoplasty (PK) served as the gold standard for addressing various corneal pathologies, including KC, demonstrating commendable graft survival rates. [ 3 ] However, PK was marred by complications, including the risk of endothelial rejection, endothelial cell loss, and various postoperative issues. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%